INDIVIDUATION PROCESS OF THE MAIN CHARACTERS IN OKKY MADASARI’S BOUND (Jurnal Pembelajaran Sastra, 2019)
The characters in the novel are a reflection of the human condition in real life. Understanding the personality of a character in a novel means understanding the personality of people too. This provides an opportunity to understand the attitudes and behavior of the people in real life through the personality of characters in literary works. Therefore, the researcher considers to discuss the process of individuation of the main characters in Okky Madasari’s Bound. The present study is literary criticism. This research aims to describe the individuation process of the main characters, Sasana and Jaka. The main characters, want the freedom to express their true identity. Through this novel, Okky Madasari wants to convey that life is a choice. Humans have the freedom to choose what they want to be without the negative side being dominant in a person. Along these lines, we can utilize Analytical Psychology to break down this novel with the idea of the individuation process. It employs the theory of individuation process proposed by Carl Gustav Jung covering several steps to achieve the process of individuation of the main characters. There are four kinds of archetypes in order to acknowledge the individuation process. They are “persona”, “shadow”, “anima and animus”, and “Self”. The results of this study show that the main characters still cannot reach the individuation process well. Sasana and Jaka have not yet reached middle age, so Sasana and Jaka have not reached self-archetype yet, because to achieve self-archetype, the characters must reach middle age first.